PEMANFAATAN BAHAN ALAM DALAM PENGOBATAN ALTERNATIF PENYAKIT PASCA BENCANA DI DESA SILIAN I, MINAHASA TENGGARA - Benedicta Irene Rumagit; Adeanne Caroline Wullur; Donald Emilio Kalonio (Dharmakarya : Jurnal Aplikasi Ipteks Untuk Masyarakat, 2022)
Silian Satu Village is one of the villages located in Silian Raya District, Southeast Minahasa Regency. This village is an area affected by the eruption of Mount Soputan where the village's position is located near the foot of the mountain. In every disaster event, many health problems are encountered. Health problems generally arise as a result of volcanic ash and gas eruptions. There is also a risk of injury whether caused by a house collapse or an accident. Health problems will increase when faced with the availability of refugee facilities with limited capacity, poor sanitation, as well as health workers or medicines available. This program aims to provide community knowledge about the use of medicinal plants in alternative medicine after a volcanic eruption disaster, community empowerment in processing the leaves of an animal into a simple dosage form (rubbing oil) for inflammation due to injury after a volcanic eruption. In addition through the use and processing of natural materials can increase the economic value of society through the processing of medicinal plants into products of economic value.